ANALISA NILAI GIZI DAN UJI ORGANOLEPTIK BOLU PEPAYA SEBAGAI ALTERNATIF MAKANAN SELINGAN PADA HIPERKOLESTEROLEMIA - Nurhamidah; Sepni Asmira; Anggia (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2022)
According to the World Health Organization (WHO) in 2018, it was recorded that people with high cholesterol in Indonesia increased every year by 28%, this number is likely to increase to 29.25 in 2025. Papaya fruit is rich in nutrition, contains high fiber and antioxidants. Papaya fruit will be processed into sponge, which is a very popular food as a snack for hypercholesterolemia. The purpose of the study was to know the average value of the color, aroma, texture, taste of the sponge and to know the value of the fiber content of the best sponge. The method used in this study is an experiment using a Completely Randomized Design method consisting of four treatments and two replications. Treatment A (25 grams of papaya), treatment B (50 grams of papaya), treatment C (75 grams of papaya) and treatment D (100 grams of papaya). This research was conducted in July 2021. Sampling was carried out at the researcher's house, while organoleptic tests were carried out at the Perintis Indonesia University campus and the fiber content inspection site at Baristand (Industrial Research and Standardization Center Padang). Based on the results of the organoleptic test, it showed that the panelists' assessment of the papaya sponge product had a very significant effect on the color, aroma, texture, and taste of the papaya sponge. Based on the panelists' assessment, treatment A (pawpaw 25 grams) was the best product, namely color 4.3; fragrance 4.56; texture 4.42 and taste 4.72 with the highest average value of 18. Treatment A contained fiber content of 5.53 with a weight of 50 grams of papaya sponge. In this study it can be concluded that the best papaya sponge is treatment A, the best papaya cake contains fiber content which is very beneficial for hypercholesterolemic patients so that it can meet fiber levels per person in a day.